The Polymycovirus-Mediated Growth Enhancement of the Entomopathogenic Fungus Beauveria bassiana Is Dependent on Carbon and Nitrogen Metabolism - Filippou, Charalampos; Diss, Rebecca M.; Daudu, John O.; Coutts, Robert H. A.; Kotta-Loizou, Ioly (Frontiers in Microbiology, 2021)
Polymycoviridae is a growing family of mycoviruses whose members typically have non-conventional capsids and multi segmented, double-stranded (ds) RNA genomes. Beauveria bassiana polymycovirus (BbPmV) 1 is known to enhance the growth and virulence of its fungal host, the entomopathogenic ascomycete and popular biological control agent Beauveria bassiana. Here we report the complete sequence of BbPmV-3, which has six genomic dsRNA segments. Phylogenetic analysis of RNA dependent RNA polymerase (RdRp) protein sequences revealed that BbPmV-3 is closely related to the partially sequenced BbPmV-2 but not BbPmV-1. Nevertheless, both BbPmV-3 and BbPmV-1 have similar effects on their respective host isolates ATHUM 4946 and EABb 92/11-Dm, affecting pigmentation, sporulation and radial growth. Production of conidia and radial growth are significantly enhanced in virus-infected isolates as compared to virus-free isogenic lines on Czapek-Dox complete and minimal media that contain sucrose and sodium nitrate. However, this polymycovirus-mediated effect on growth is dependent on the carbon and nitrogen sources available to the host fungus. Both BbPmV-3 and BbPmV-1 increase growth of ATHUM 4946 and EABb 92/11-Dm when sucrose is replaced by lactose, trehalose, glucose or glycerol, while the effect is reversed on maltose and fructose. Similarly, both BbPmV-3 and BbPmV-1 decrease growth of ATHUM 4946 and EABb 92/11-Dm when sodium nitrate is replaced by sodium nitrite, potassium nitrate or ammonium nitrate. In conclusion, the effects of polymycoviruses on B. bassiana are at least partially mediated via its metabolic pathways.